Los principios del Derecho de la inteligencia artificial.: Una propuesta de hard law - Jaramillo Romero, Saulo (2025)
The use and application of artificial intelligence (AI) produces negative impacts on individuals, such as the violation of human and fundamental rights. In this paper, the principles of AI Law are proposed as an alternative for binding and obligatory regulation. In this sense, a theoretical-doctrinal study is carried out, from its origin, its passage through ethics, soft law documents, and the need for its positivization. To this end, using the qualitative method and the document analysis technique, doctrinal and institutional studies were analyzed, through which they have been developed and consolidated. The state of the art verifies that there is a doctrinal and legal agreement on six principles of AI Law: pro-person, transparency, beneficence, non-maleficence, equity, and responsibility. However, because they are ethical and indicative guidelines, they are insufficient for the development and use of human-centered AI and algorithmic transparency. As a hard law proposal, observing the reconfiguration of the social pact and the recognition of new rights such as the human right to the internet, neuro-rights (privacy and mental intimacy), and the right to human control, the need for its positivization is substantiated.